Rhizobium Impacts on Seed Productivity, Quality, and Protection of Pisum sativum upon Disease Stress Caused by Didymella pinodes: Phenotypic, Proteomic, and Metabolomic Traits - Ranjbar Sistani, Nima; Kaul, Hans-Peter; Desalegn, Getinet; Wienkoop, Stefanie (Frontiers in Plant Science, 2017)
In field peas, ascochyta blight is one of the most common fungal diseases caused by Didymella pinodes. Despite the high diversity of pea cultivars, only little resistance has been developed until to date, still leading to significant losses in grain yield. Rhizobia as plant growth promoting endosymbionts are the main partners for establishment of symbiosis with pea plants. The key role of Rhizobium as an effective nitrogen source for legumes seed quality and quantity improvement is in line with sustainable agriculture and food security programs. Besides these growth promoting effects, Rhizobium symbiosis has been shown to have a priming impact on the plants immune system that enhances resistance against environmental perturbations. This is the first integrative study that investigates the effect of Rhizobium leguminosarum bv. viceae (Rlv) on phenotypic seed quality, quantity and fungal disease in pot grown pea (Pisum sativum) cultivars with two different resistance levels against D. pinodes through metabolomics and proteomics analyses. In addition, the pathogen effect on seed quantity components and quality is assessed at morphological and molecular level. Rhizobium inoculation decreased disease severity by significant reduction of seed infection level. Rhizobia symbiont enhanced yield through increased seed fresh and dry weight based on better seed filling. Rhizobium inoculation induced changes in seed proteome and metabolome involved in enhanced P. sativum resistance level against D. pinodes. Besides increased redox and cell wall adjustments light is shed on the role of Late Embryogenesis Abundant proteins and metabolites such as the seed triterpenoid Soyasapogenol. The results of this study open new insights into the significance of symbiotic Rhizobium interaction for crop yield, health and seed quality enhancement and reveal new metabolite candidates involved in pathogen resistance.